Aberrant phenotypes of transgenic mice expressing dimeric human erythropoietin - Yun Seong-Jo; Naidansuren Purevjargal; Sim Bo-Woong; Park Jong-Ju; Park Cha-Won; Nanjidsuren Tseeleema; Kang Myung-Hwa; Hwang Sue-Yun; Yoon Jong-Taek; Min Kwan-Sik (BMC, 2012)
Abstract Background Dimeric human erythropoietin (dHuEPO) peptides are reported to exhibit significantly higher biological activity than the monomeric form of recombinant EPO. The objective of this study was to produce transgenic (tg) mice expressing dHuEPO and to investigate the characteristics of these mice. Methods A dHuEPO-expressing vector under the control of the goat beta-casein promoter, which produced a dimer of human EPO molecules linked by a 2-amino acid peptide linker (Asp-Ile), was constructed and injected into 1-cell fertilized embryos by microinjection. Mice were screened using genomic DNA samples obtained from tail biopsies. Blood samples were obtained by heart puncture using heparinized tubes, and hematologic parameters were assessed. Using the microarray analysis tool, we analyzed differences in gene expression in the spleens of tg and control mice. Results A high rate of spontaneous abortion or death of the offspring was observed in the recipients of dHuEPO embryos. We obtained 3 founder lines (#4, #11, and #47) of tg mice expressing the dHuEPO gene. However, only one founder line showed stable germline integration and transmission, subsequently establishing the only transgenic line (#11). We obtained 2 F1 mice and 3 F2 mice from line #11. The dHuEPO protein could not be obtained because of repeated spontaneous abortions in the tg mice. Tg mice exhibited symptoms such as short lifespan and abnormal blood composition. The red blood cell count, white blood cell count, and hematocrit levels in the tg mice were remarkably higher than those in the control mice. The spleens of the tg mice (F1 and F2 females) were 11- and -21-fold larger than those of the control mice. Microarray analysis revealed 2,672 spleen-derived candidate genes; more genes were downregulated than upregulated (849/764). Reverse transcriptase-polymerase chain reaction (RT-PCR) and quantitative real-time PCR (qRT-PCR) were used for validating the results of the microarray analysis of mRNA expression. Conclusions In conclusion, dHuEPO tg mice caused excessive erythrocytosis that led to abnormal blood composition, short lifespan, and abnormal splenomegaly. Further, we identified 2,672 genes associated with splenomegaly by microarray analysis. These results could be useful in the development of dHuEPO-producing tg animals.